2018
DOI: 10.1039/c7ra13726e
|View full text |Cite
|
Sign up to set email alerts
|

Shunaoxin dropping pill, a Chinese herb compound preparation, attenuates memory impairment in d-galactose-induced aging mice

Abstract: The Shunaoxin dropping pill (SNX) is derived from a traditional recipe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Additionally, it was reported that the hippocampus is closely related to learning and memory activity (He et al., 2009). Overactivated astrocytes can intensify oxidative stress by reducing the number of neurons, inhibiting synaptic transmission, and releasing cytotoxic or neurotoxic substances, thus affecting the normal neuronal function and leading to cognitive impairment (Hou et al., 2019; Wang et al., 2014; Zhou et al., 2018). The expression of NeuN (Figure 8b) in the hippocampus was elevated after MAN administration, indicating that MAN can promote the regeneration of neurons in aging mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was reported that the hippocampus is closely related to learning and memory activity (He et al., 2009). Overactivated astrocytes can intensify oxidative stress by reducing the number of neurons, inhibiting synaptic transmission, and releasing cytotoxic or neurotoxic substances, thus affecting the normal neuronal function and leading to cognitive impairment (Hou et al., 2019; Wang et al., 2014; Zhou et al., 2018). The expression of NeuN (Figure 8b) in the hippocampus was elevated after MAN administration, indicating that MAN can promote the regeneration of neurons in aging mice.…”
Section: Discussionmentioning
confidence: 99%
“…SK-N-SH cells treated with H 2 O 2 for 24 h showed a dose-dependent cytotoxic effect, an increase in oxidative stress, activated caspase 3 activity, and acetylcholinesterase (AChE) inhibition activity (Sattayasai et al, 2013). In another study, the administration of 100 μm of H 2 O 2 to PC12 cells for 2 h suppressed the proliferation of cells and promoted shrinkage in the cell body, the release of LDH, increases in intra-cellular ROS, extra cellular NO, loss of MMP, which further induce apoptosis and damage dendritic networking, thereby inducing cell death (Xu et al, 2016;Zhou et al, 2018; Figure 4).…”
Section: Hydrogen Peroxidementioning
confidence: 99%